Counseling on the Utilization of Fruit Waste as an Alternative to Liquid Organic Fertilizer in the Tangga Takat Village, District of Seberang Ulu II, Palembang City - Nurbaiti Amir; Berliana Palmasari; Ika Paridawati; Dessy Tri Astuti; Ahmad Sofian; Neni Marlina (Altifani Journal: International Journal of Community Engagement, 2023)
Fruit waste is considered a waste material that cannot be used anymore, so that its existence has not been properly utilized by the community. Even though fruit waste can still be reused as material for making liquid organic fertilizer (POC). Liquid organic fertilizer made from fruit waste is a type of fertilizer that has many benefits, both for plants and the environment. Liquid organic fertilizer is environmentally friendly and safe for humans and animals. Liquid organic fertilizer also improves soil structure, increases soil fertility, and increases soil water holding capacity, besides being environmentally friendly, reduces soil pollution, and protects soil health. This community service activity aims to provide knowledge and skills to the community about reusing fruit waste by processing it into liquid organic fertilizer (POC). The location of the community service was carried out at the Tangga Takat village head office, Seberang Ulu II District, Palembang City, on February 24 2022. The method used was counseling and training for the community about processing fruit waste into liquid organic fertilizer. This activity brought together 25 enthusiastic participants in a discussion and question and answer session during the training. The results of this community service show that the method of community service in the form of consultation, training and question and answer is very suitable for motivating the community in processing fruit waste into liquid organic fertilizer.